Basic gymnastics as a basic component invariant component of the curriculum subject «Physical culture» - Дейнеко Альфія Хамзіївна (Alfiya Deyneko) (Slobozhanskyi Herald of Science and Sport, 2015)
Purpose: the analysis of the program discipline «Physical education» for grades 1–9 students in the context of the use of basic gymnastics. Material and Methods: the primary means of gymnastics, studied by pupils of 1–9 forms, was investigated as a part of the curriculum «Physical education in school». The study examined the content of primary invariant of gymnastics lesson. Results: it is found that the formation of school culture movements (movements exploring their diversity, physical exercises, etc.) is in elementary school; due to the introduction of the learning material secondary school pupils gymnastic movements increased complexity is creating a culture of performance and use of basic gymnastics exercises that are the basis of the general culture of motor activity. Conclusions: the main factor reducing the general level of motor culture of pupils identified as a lack of training programs for grades 5–11 clearly defined lines of content on the use of basic gymnastics.